Implementasi Peraturan Walikota Nomor 43 Tahun 2012 Tentang Peraturan Pelayanan Administrasi Terpadu Kecamatan (PATEN) di Kecamatan Gunungpati dan Kecamatan Semarang Barat Kota Semarang - DHIYA JIHAN TIFANA; Yuwanto . (Journal of Politic and Government Studies, 2020)
One of the government's efforts in realizing Good Government is bymaking a policy, namely the Integrated District Administration Service(PATEN). PATEN was created to realize the Subdistrict as a communityservice center and become a service node for SKPD which aims to improvethe quality and bring services closer to the people of Semarang City. In thisstudy presents an overview of the implementation of PATEN in GunungpatiDistrict and Semarang Barat District. The research method used isdescriptive qualitative with data collection techniques in the form ofinterviews and documentation. The data obtained were then analyzed usingTriangulation Methods, Theory, and Data Sources.Findings This research is a type of PATEN licensing services in thecity of Semarang, especially in Gunungpati District and West SemarangDistrict there has been no delegation of authority from the Mayor to theDistrict Head. So that the PATENT service in the District is only the type ofnon-licensing services that can be administered by the District. People whowant to submit an application for the type of licensing service only get aletter of recommendation from the District, therefore the community musttake care to the next stage, namely in the relevant Dinas.The conclusion that can be drawn from the research is that first inthe journey of PATENT in Semarang City from 2012 until now there has notbeen any delegation of authority in the type of licensing services. Secondly,PATEN in Gunungpati Subdistrict and West Semarang Subdistrict broughtgreat changes to the service standards and infrastructure of the Subdistrictgetting better. Based on the conclusions, the suggestions that can be givenare that it would be better for the government to only focus on one licensingservice policy, so that there is no overlapping of the duties and functions ofa licensing service policy.Keywords: Good Government, Policy Implementation, PublicServices